2018
DOI: 10.1088/2040-8986/aaa6f7
|View full text |Cite
|
Sign up to set email alerts
|

High-order harmonic generation driven by inhomogeneous plasmonics fields spatially bounded: influence on the cut-off law

Abstract: We study high-order harmonic generation (HHG) in model atoms driven by plasmonic-enhanced fields. These fields result from the illumination of plasmonic nanostructures by few-cycle laser pulses.We demonstrate that the spatial inhomogeneous character of the laser electric field, in a form of Gaussian-shaped functions, leads to an unexpected relationship between the HHG cutoff and the laser wavelength. Precise description of the spatial form of the plasmonic-enhanced field allows us to predict this relationship.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Additionally, from the results corresponding to the inhomogeneous case, a noticeable increasing of the photoelectron yield is also observed. Previously, this effect was observed in the photon flux [23]. In that paper was reported that many electron trajectories did not recombine with their parents ions, so a large direct ATI yield could be expected.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Additionally, from the results corresponding to the inhomogeneous case, a noticeable increasing of the photoelectron yield is also observed. Previously, this effect was observed in the photon flux [23]. In that paper was reported that many electron trajectories did not recombine with their parents ions, so a large direct ATI yield could be expected.…”
Section: Resultsmentioning
confidence: 85%
“…Additionally, the field distribution is normalized with respect to the strength at point A. The electric field distribution is then constructed by using two Gaussian functions [23]. The maximum associated laser intensity is 3 orders of magnitude larger than the excitation laser intensity, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…the linear term: h(x) = x. This choice is motivated by previous investigations [83,85,86], but nothing prevents to use more general functional forms for h(x) [87]. The actual spatial dependence of the enhanced nearfield in the surrounding of a metal nanostructure can be obtained by solving the Maxwell equations incorporating both the geometry and material properties of the nanosystem under study and the input laser pulse characteristics (see e.g.…”
Section: A Quantum Approachesmentioning
confidence: 99%
“…One of the main advantages of the 1D-TDSE is that we are able to include any functional form for the spatial variation of the plasmonic field. For instance, we have implemented linear [83] and real (parabolic) plasmonic fields [84], as well as near-fields with exponential decay (evanescent fields) [88] and gaussian-like bounded spatially fields [87].…”
Section: A Quantum Approachesmentioning
confidence: 99%
“…One year later, J. Armstrong, N. Bloembergen et al [2] published the fundamental paper, dealing with the optical frequency conversion, in which the coupled nonlinear equations were developed and many explicit solutions of these equations were obtained in the framework of the plane wave approximation. During passed decades the SHG was widely observed: in plasma optics [35] and nonlinear optics, including high-harmonic generation [612], and in a medium containing nanoparticles [13, 14], and in semiconductor [15]. In [16] the SHG at the boundary between dielectric media is analyzed.…”
Section: Introductionmentioning
confidence: 99%